Tourisme, gestion sociale de l’eau et changement climatique dans un territoire de haute altitude : le massif de l’Everest au Népal - Marie Faulon; Isabelle Sacareau (Revue de Géographie Alpine)
This paper deals with the relationship between water, tourism and climate change in the touristy highland region of the Everest in Nepal. Tens of thousands of trekkers visit yearly this valley drained by the Dudh Koshi and its tributaries. We question water availability for tourism needs, assuming that the observed supply difficulties might be caused by the social management of the resource rather than the iffy effects of climate change. We show that the evolution regarding the way people trek brings new needs in water and electricity. It results in a new pressure on water resources since the touristy season and the hydrologic regime are misaligned. However, the pressure must be put into perspective with regard to the way inhabitants organize and plan the infrastructures for collecting and withdrawing water from the rivers. Our analyses show strong inequalities in the access of water at two distinct scales, between villages and within villages, as well as a high territorial fragmentation of water and electricity networks. They bear witness to a complex social management of water and a lack of coordination at the valley scale, which threatens the sustainability of the infrastructures as well as the tourist economy.